Evaluation the temperature of rangue-hilsch vortex tube performance using taguchi method - Law, Seong Seng (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The output performances of vortex tube are mainly depending on the vortex tube parameters (length, diameter and angle). A study was carried out to investigate the relationship between the vortex tube parameters and the output performance of a vortex tube. Therefore, the objective is to study the effect of those vortex tube parameters on the output air temperature. The lowest temperature to be produced must be less than 10C then Taguchi method was used to optimize the vortex tube parameters.